Spatial distribution of tumor-infiltrating T cells indicated immune response status under chemoradiotherapy plus PD-1 blockade in esophageal cancer - Yan, Cihui; Huang, Hui; Zheng, Zhunhao; Ma, Xiaoxue; Zhao, Gang; Zhang, Tian; Chen, Xi; Cao, Fuliang; Wei, Hui; Dong, Jie; Tang, Peng; Jiang, Hongjing; et al. (Frontiers in Immunology, 2023)
Background: The spatial distribution of tumor-infiltrating T cells and its dynamics during chemoradiotherapy combined with PD-1 blockade is little known in esophageal squamous cell carcinoma (ESCC). Methods: We applied multiplex immunofluorescence method to identify T cells (CD4+, CD8+ T cells, and their PD-1- or PD-1+ subsets) and myeloid-derived cells (CD11c+ dendritic cells, CD68+ macrophages, and their PD-L1+ subpopulations) in paired tumor biopsies (n = 36) collected at baseline and during combination (40 Gy radiation) from the phase Ib trial (NCT03671265) that ESCC patients treated with first-line chemoradiotherapy plus anti-PD-1 antibody camrelizumab. We used the FoundationOne CDx assay to evaluate tumor mutation burden (TMB) in baseline tumor biopsies (n = 14). We dynamically assessed the nearest distance and proximity of T-cell subsets to tumor cells under combination, and estimated the association between T-cell spatial distribution and combination outcome, myeloid-derived subsets, TMB, and patient baseline characteristics. Findings: We found tumor compartment had lower T-cell subsets than stromal, but maintained comparable level under combination. Both before and under combination, PD-1- T cells located closer than PD-1+ T cells to tumor cells; T cells, dendritic cells, and macrophages showed the highest accumulation in 5-10 μm distance. Higher CD4+ T cells in tumor compartment, and shorter nearest distance of T-cell subsets at baseline predicted poor OS. Higher baseline CD4+ T cells, dendritic cells, and macrophages was associated with worse OS in less than 10 μm distance to tumor cells, but related with better OS in farther distance. Higher on-treatment PD-1 positive-expressed CD4+ and CD8+ T cells within 100 μm distance to tumor cells predicted longer OS. T cells, dendritic cells, and macrophages showed positive spatial correlation. Both high TMB and smoking history were associated with closer location of T cells to tumor cells at baseline. Conclusions: We firstly illustrated the T-cell spatial distribution in ESCC. Combing chemoradiotherapy with PD-1 blockade could improve the anti-tumor immune microenvironment, which benefit the treatment outcome. Further understanding the precision spatiality of tumor-infiltrating T cells would provide new evidence for the tumor immune microenvironment and combination treatment with immunotherapy.